Efektivitas Penggunaan Media Buku Saku dalam Pembelajaran Pendidikan Kewarganegaraan untuk Menumbuhkan Cinta Budaya Daerah Siswa (Studi Kuasi Eksperimen pada Siswa Kelas VII SMP Negeri 5 Malang) - Maya Mashita (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2016)
This study aims to determine effective use of instructional media pocket book on learning Civic Education to foster a culture of love student area. The approach used in this study is a quantitative approach with a quasi-experimental methods and research design is pretest and posttest control group. The study used a sample of students in grades 7.1 and 7.2 SMP Negeri 5 Malang. Instrument used in this study was a questionnaire, test, attitude scale, and performance tests. Data analysis technique used is Independent Samples Test. The results showed that: 1) there are differences in knowledge of the love of local culture significantly between the experimental class with a grade control, 2) there are differences in the attitude of the love of local culture significantly between the experimental class with a grade control, and 3) there are different skills love culture that significant between the experimental class with a grade control class.